Budget impact analysis on the introduction of a guideline based hepatitis B and C screening into a routine check-up in the German primary care setting. (2nd January 2018) - Barth, Cordula; Neusser, Silke; Biermann, Janine; Wasem, Jürgen; Berg, Thomas; Wiegand, Johannes; Wolffram, Ingmar; Petroff, David; Aidelsburger, Pamela; Grünbauer, Alexandra; Neumann, Anja
Abstract: Objectives: Systematic screening for chronic hepatitis B and C does not yet exist in Germany. Therefore, the implementation of a screening approach within a preventive medical examination performed by primary care physicians ('Check-Up 35+') was evaluated in a recent prospective multicenter study. The present analysis estimates the financial consequences for the statutory health insurance by budget impact analysis. Materials and methods: A Markov cohort model was developed consisting of 21 health states. Four different screening scenarios derived from the previous multicenter study were compared to usual care, a strategy without screening for hepatitis. Actual cost data for Germany were calculated and systematic literature searches for all input parameters were performed. Results: The base case results in incremental costs for the screening strategies compared to no hepatitis screening of 165–227 € per patient in a 20-year horizon. Two main parameters influence the financial consequences: (A) detection and treatment increase the costs in the beginning. (B) Screening avoids hepatitis induced end-stage liver disease. The initial higher costs exceed the later savings. Sensitivity analyses demonstrate a strong impact of medication costs for the treatment of additionally detected hepatitis infections on the outcome. This finding is robust to sensitivity analysis. Conclusions: The screening strategy proposed here implies additional costs for the statutory health insurance, however, a decision regarding its usefulness must consider criteria other than cost. For example, the high burden of disease due to liver cirrhosis and liver carcinoma should be considered. Therefore, an additional cost-effectiveness-analysis should be conducted.